1992
DOI: 10.1002/app.1992.070440116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on mechanical properties of epoxy resin filled with angular‐shaped silica

Abstract: SYNOPSISEffect of particle size on the mechanical properties of cured epoxy resins has been studied. Resin was filled with angular-shaped silica particles prepared by crushing fused natural raw quartz. These particles were sorted into six groups having different mean sizes ranging from 2-47 pm. Flexural and compressive moduli of the cured epoxy resin slightly decreased with decrease in the particle size of the silica, whereas tensile modulus slightly increased. Flexural and tensile strengths increased with dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 13 publications
1
55
0
Order By: Relevance
“…It has a reported inherent viscosity of 0.87 dL/g measured at a concentration of 0.5 g/dL in H 2 SO 4 . The particulate used in the preparation of composites was Al 2 O 3 powder of density 4.00 g/cm 3 . It was used as supplied by Aldrich Chemical Company.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a reported inherent viscosity of 0.87 dL/g measured at a concentration of 0.5 g/dL in H 2 SO 4 . The particulate used in the preparation of composites was Al 2 O 3 powder of density 4.00 g/cm 3 . It was used as supplied by Aldrich Chemical Company.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] The addition of inorganic fillers or particles to a polymer has been a common practice to improve the mechanical properties. Among inorganic fillers, calcium carbonate has been one of the most commonly used fillers for commodity plastics such as HDPE 6 and polypropylene (PP), 7 to reduce the cost of the expensive resins.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the decrease in particle size can increase the strength as long as the particles are well dispersed (Nakamura et al 1992;Pukanszky and Vörös 1993;Radford 1971).…”
Section: Introductionmentioning
confidence: 99%
“…They include the aspect ratio of the filler [5,17], the orientation of the fillers, interfacial interaction and the nature of the failure [5]. From the studies reported [18,24,[28][29][30][31][32][33][34][35][36], it seems that there is a critical particle size, usually in nanoscale, above which there is no effect on Treated Titanium Dioxide Dispersion/Natural Rubber Latex composite modulus. When the particle size is below this critical value, the effect on composite modulus is more significant.…”
Section: Resultsmentioning
confidence: 99%